Clouds on the hot Jupiter HD189733b: constraints from the reflection spectrum - Barstow, J; Aigrain, S; Irwin, P; Hackler, T; Fletcher, L; Lee, J; Gibson, N (Institute of Physics Publishing, 2014)
The hot Jupiter HD 189733b is probably the best studied of the known extrasolar planets, with published transit and eclipse spectra covering the near UV to mid-IR range. Recent work on the transmission spectrum has shown clear evidence for the presence of clouds in its atmosphere, which significantly increases the model atmosphere parameter space that must be explored in order to fully characterise this planet. In this work, we apply the NEMESIS atmospheric retrieval code to the recently published HST/STIS reflection spectrum, and also to the dayside thermal emission spectrum in the light of new Spitzer/IRAC measurements, as well as our own re-analysis of the HST/NICMOS data. We first use the STIS data to place some constraints on the nature of the cloud on HD189733b, and explore solution degeneracy between different cloud properties and the abundance of Na in the atmosphere; as already noted in previous work, absorption due to Na plays a significant role in determining the shape of the reflection spectrum. We then perform a new retrieval of the temperature profile and abundances of H2O, CO2, CO and CH4 from the dayside thermal emission spectrum. Finally, we investigate the effect of including cloud in the model on this retrieval process. We find that the current quality of data does not warrant the extra complexity introduced by including cloud in the model; however, future data are likely to be of sufficient resolution and signal-to-noise that a more complete model, including scattering particles, will be required.